Analisis Perbandingan Struktural dan Karakteristik Badan Usaha Milik Negara Indonesia Dengan Malaysia - Fathurrahman, Raihan (UI Scholars Hub, 2024)
The comparative analysis of the structural and characteristic aspects of State-Owned Enterprises (BUMN) in Indonesia and Malaysia highlights differences in their approaches to managing these state-owned companies. In Indonesia, BUMN are regulated by Law No. 19 of 2003, which divides BUMN into Persero and Perum. However, bureaucratic structures with strict hierarchies and political intervention often hinder market efficiency and responsiveness. Meanwhile, Government-Linked Companies (GLCs) in Malaysia, under the supervision of Khazanah Nasional Berhad, demonstrate a more streamlined and flexible structure. They operate with higher autonomy and tight supervision, enabling quicker responses to market changes. In terms of governance, Indonesia applies the principles of good corporate governance, but political intervention remains a significant challenge. On the other hand, GLCs in Malaysia emphasize transparency and accountability, supported by the Government-Linked Company Transformation Program (GLCT) aimed at enhancing performance and competitiveness. These differences result in contrasting performances; BUMN in Indonesia are often hampered by bureaucracy and political intervention, while GLCs in Malaysia are more efficient and competitive due to their centralized structure and strict supervision. Recommendations to enhance BUMN performance include adopting a centralized management model in Indonesia and promoting innovation and adaptation in Malaysia.